Synesthesia: The Synthesis of Arts in World Art Culture: Abstracts from a Conference held in Saint Petersburg, March 4–5, 2019 - Jewanski, Jörg; Nikolaeva, Nina; Konanchuk, Svetlana (2020)
This book provides abstracts of papers of the 2nd International Conference Polylogue and Synthesis of Arts: History and Modernity, Theory and Practice; Epochs – Styles – Genres, which took place on March 4–5, 2019, at the Rimsky-Korsakov Saint Petersburg State Conservatory. The conference was dedicated to Music and its relationship to Philosophy, Literature, and the Visual Arts. While papers were presented predominantly by Russian academicians, a range of authors participated from Western European, United States and Far East academies, including from China and Mongolia. In this way, the conference’s agenda was expanded to worldwide cultures. The original conference proceeding was published in Russian in 2019; it was subsequently translated into English and revised for this present edition. The limited availability of Russian academic publications in the West, combined with a language barrier, create considerable constraints in the way of wider recognition. We aim to address this gap by offering readers this English edition as a source for a broader appreciation in the West of contemporary Russian research.Permalinkhttps://nbn-resolving.de/urn:nbn:de:hbz:6-01149499132ISBN978-3-8405-0230-9Paperback, 200 Seiten